Joint Beamforming and Power Control Algorithm for Cognitive MIMO System via Game Theory - Qing Peng; Yinwei Li; Zhijun Guo (Dianxin kexue)
The optimization problem of joint beamforming and power for cognitive MIMO system was studied.Firstly，a non-cooperative separable game model was established and a cost function about the two parameters was put forward.Then it was concluded that the optimal Nash equilibrium of joint game exists by proving the existence of optimal Nash equilibrium of two sub-games through KT conditions.Finally，a new iterative algorithm alternately was presented.The simulation results demonstrate that the proposed algorithm has a faster convergence rate.Meanwhile，the algorithm also comes to the optimal Nash equilibrium and has perfect stability in the dynamic communication environment.